Critically Analyzing the Role of Total Rewards and Compensa-tion in Increasing Employee Motivation - Seema Bhakuni; Sandeep Saxena (PT FORMOSA CENDEKIA GLOBAL, 2023)
Employees are the main assets for an organisation and motivating the employees can improve their performance. Several ways can be incorporated for employee motivation. The objective of this research is to understand the role of Total Rewards and Compensation in increasing employee motivation. Materials and methods: Survey has been conducted by incorporating 80 participants and the survey results has been analysed with the help of SPSS software. Findings: The result conveys that there is a positive relation between employee motivation and engagement. Conclusion: Employee motivation has strong relation with employee engagement and increasing organisational performance. Employee motivation can create positive working culture within the workplace. Significance of the study: The research will contribute to understand the role of compensation and total rewards in case of employee motivation. Besides this, this research is also helpful to understand the importance of employee motivation in case of organisational performance